Analisis Tantangan Pendidikan Islam di Kabupaten Bone pada Era Modern - Andi Muh. Anugrah Paerah Mansur; Asdar, Asdar; Idrus L (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the challenges of Islamic education in Bone Regency within the context of modern transformation characterized by digitalization, globalization, and technological disruption. Employing a non-empirical library research approach, the study synthesizes relevant academic literature to construct a comprehensive and critical understanding of the issue. The findings reveal that Islamic education faces multidimensional challenges, including structural limitations, curriculum misalignment, and evolving societal expectations influenced by global trends. These challenges are further intensified by the need to maintain religious identity while adapting to contemporary educational demands. The analysis highlights that the sustainability of Islamic education depends on its ability to adopt adaptive and integrative strategies, particularly through the integration of religious and scientific knowledge, innovation in digital pedagogy, and strengthening institutional governance. Moreover, collaborative engagement among stakeholders is identified as a crucial factor in fostering a resilient educational ecosystem. The study concludes that a contextual and transformative approach is essential to ensure that Islamic education remains relevant, competitive, and value-oriented in the modern era.